Integrating quantitative and qualitative data in mixed methods research: An illustration - Hands, Africa S. (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2022)
Employing a mixed methods approach to research is meant to deliver a comprehensive examination of the phenomenon under study. An integral step in mixed methods research is integrating qualitative and quantitative data. However, published reports rarely detail the process of mixing data from both approaches. Presented here is an illustration of integrating qualitative and quantitative data sets using a convergence table. A review of mixed methods research in LIS is presented, and a reflection on the challenges of integration is shared. As the mixed methods approach increases in LIS research, the example offered here aims to make integration more transparent.